Analisis Strategi Pembelajaran Sains Berbasis Salingtemas dalam Membangun Sikap Ilmiah Siswa: sebuah Tinjauan Literatur Sistematis - Sulthon (Indonesian Journal of Islamic Elementary Education, 2024)
The advancement of science will boost technology, technological advancement will bring negative and positive impacts in life, so that students have concern, awareness, scientific attitude and are responsible for their environment, so quality science learning is needed to prevent environmental damage. This study aims to describe science learning with salingtemas to build students' scientific attitudes. The method used in this study is the Systematic Literature Review method, which is a research method to identify, study, evaluate, and interpret data systematically through searching for journal articles from the Google Scholar and Publish or Perish 8 databases published from 2018 to 2024 from the journal search 208 articles were obtained, after being filtered into 34 articles, then selected using the keywords "salingtemas" and "science learning approach" a study of 27 articles was obtained then adjusted again to the specific needs of the research article and obtained 9 articles, this will then be analyzed. The results of the study show that science learning with a mutual-theme approach can improve scientific attitudes, critical thinking, creativity, discipline, sensitivity, objectivity, care, cooperation, and responsibility towards oneself and protecting the environment from the negative impacts of the use of technology in life.